Cerita bergambar kuliner seru bersama sahabat buah: media alternatif edukasi pemilihan jajanan sehat - Septian Emma Dwi Jatmika; Farikhah Nur Laila; Mufidatusholihah Mufidatusholihah; Ravika Andinie; Fitri Rekyan MWH (Universitas Ahmad Dahlan, 2021)
Children often have problems with snacks. They need health education to be able to choose healthy foods to meet optimal nutritional intake. This study aims to see the effect of using picture book media on increasing knowledge about healthy culinary tourism at Public Elementary School Gedongkiwo Yogyakarta. This type of study is quasi-experimental research. The survey designed is One Group Pretest Post Test Design. The research participants were 25 grade 2 elementary school students. The data analysis technique used the Paired Sample T-Test statistical test. The result obtained is that picture books do not affect knowledge about healthy culinary tourism (p-value 0.770> 0.05). A total of 9 students experienced a decrease in their level, seven students experienced an increase, and nine students did not experience a reduction or increase in knowledge. It is possible because the method used is combining lectures with visual story media during class. The conditions are different if students read pictorial stories themselves during leisure time. The next researcher will be able to study using a more simple method, for example, while having group discussions so that there is a two-way exchange of information.